Gaya Bahasa Kiasan Dalam Puisi “Mansyūrātun Fidāiyyatun ‘Alā Judrāni Isrāīl” - Loita Kurrota A'yun (Arabiyatuna: Jurnal Bahasa Arab, 2018)
A poet often uses the style of language in composing poetry in order to achieve the desired beauty. Likewise with one of the famous Arab poets in the modern era, namely Nizar Qabbani. He often uses language styles, one of which is the figurative language style, to compose verses in his poems. One of his works which contains a lot of this style of figurative language is his poem entitled "Mansyūrātun Fidāiyyatun ā Al Judrāni Isrāīl". This study aims to analyze the style of figurative language used in the poem. In this study, researchers used stylistic analysis, to be able to find out the types of figurative language used by poets. The results of this study indicate that poets use several kinds of figurative language styles, namely equation or simile (tasybīh), metaphor or isti’ārah, antonomasia or kināyah, pars pro toto (majāz mursal juz’iyyah), irony and cynicism. The most figurative style of speech used by poets is the style of equality or simile (tasybīh), irony and cynicism. This is because the poem is a criticism and representation of expressions of bitterness, anger, and disappointment of the Palestinian people both towards Israel, America, and other world communities.